“If the End Justifies the Means, Then This Is Permissible…”: Academic Deviations of Russian Postgraduate Students in Socio-Humanitarian Areas - M. A. Kashina; V. A. Vasilyeva; S. Tkach (Высшее образование в России)
This article looks at academic deviation practices from the viewpoint of graduate students, as well as whether or not they find certain types of deviant behavior in science and education acceptable. The theoretical framework consisted of two mutually exclusive approaches to the interpretation of academic deviations: the normativist R. Descartes and the epistemic anarchism of P. Feyerabend. The study purpose is to evaluate graduate students in socio-humanitarian scientific specializations regarding the prevalence and attitude toward academic deviation. Main hypothesis: postgraduate students’ views regarding academic deviations, especially plagiarism, fall on a continuum, ranging from total denial to total acceptance. Research design: quantitativequalitative. Empirical base: online survey (1276 respondents, including 185 graduate students), 5 focus groups. Methods of analysis: cluster analysis using the k-nearest neighbors method, qualitative analysis of focus group materials. Main results. It was discovered that creating crib sheets was the most prevalent form of academic deviation among graduate students. Of the respondents, 66% selected “often” and “very often” as their options. The purchase of exams, abstracts, and coursework showed the least amount of variation. Ten percent of those surveyed said that graduate students used plagiarism frequently or extremely frequently. Based on their attitudes regarding plagiarism, five distinct groups could be identified using cluster analysis, three of which would be more tolerant of it. Simultaneously, two of the five groups place the blame on students, and three see plagiarism as a result of the educational system’s failure to some extent. Directions for further research are related to the analysis of other forms of deviation, for example, practices of academic collusion within a university, as well as a description of the objective reasons for graduate students committing academic deviations, consideration of the prevalence of academic deviations of graduate students as a sign of a crisis in the normative foundations of the institution of graduate school.